Measurements of drag and lift on smooth balls in flight. (12th May 2017) - Cross, Rod; Lindsey, Crawford
Abstract: Measurements are presented on the drag and lift coefficients for three relatively smooth balls launched in air and tracked with two cameras separated horizontally by 6.4 m. The ball spin was varied in order to investigate whether the Magnus force would increase or decrease when the ball spin was increased. For one ball, the Magnus force increased. For another ball, the Magnus force decreased almost to zero after reaching a maximum. For the third ball, the Magnus force was negative at low ball spins and positive at high ball spins. For one of the balls, the ball spin increased with time as it travelled through the air.